Interplay of Auditor Rotation, Firm Size, and Audit Quality: An Empirical Investigation - Sumartono, Sumartono; Pasolo, Muhammad Ridhwansyah; Ermawati, Yana; Sonjaya, Yaya (Advances in Managerial Auditing Research, 2023)
Purpose: This study explores the impact of auditor retention and firm size on audit quality, emphasizing their relevance to audit independence and corporate governance. Understanding these factors is crucial for regulators and businesses aiming to enhance financial reporting quality. Research Design and Methodology: The study focuses on 15 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Using secondary data from IDX records, logistic regression analysis was conducted to examine the relationships between auditor retention, firm size, and audit quality. Findings and Discussion: The findings show that auditor retention has a negative and insignificant effect on audit quality, indicating that frequent auditor changes do not necessarily improve audit outcomes. Similarly, firm size negatively and insignificantly affects audit quality, suggesting that larger companies do not always receive superior audits. These results challenge the belief that auditor rotation and firm size are primary indicators of audit quality. Implications: The study suggests that companies should prioritize auditor competence over rotation policies, while regulators may need to reassess mandatory auditor rotation’s effectiveness. Future research should consider other factors, such as auditor tenure, audit fees, and corporate governance, to gain a more comprehensive understanding of audit quality determinants. These insights can guide policymakers in enhancing audit standards and financial reporting integrity.